Prenatal exposure to polybrominated diphenyl ethers and birth outcomes. (November 2015) - Chen, Limei; Wang, Caifeng; Cui, Chang; Ding, Guodong; Zhou, Yijun; Jin, Jun; Gao, Yu; Tian, Ying
Abstract: This study aimed to examine the potential association between maternal PBDEs and birth outcomes, including birth weight (g), length (cm), head circumference (cm) and gestational age (week). 215 mothers were recruited from a prospective birth cohort in rural northern China between September 2010 and February 2012. Serum PBDE congeners were detected and their association with birth outcomes were examined. The median maternal serum concentrations of BDE-28, -47, -99, -100, -153 were 2.27, 2.26, 3.58, 2.13, 4.87 ng/g lipid, respectively. Maternal LgBDE-28 and LgBDE-100 were negatively associated with birth length (β = −0.92, 95% confidence interval (CI): −1.82,  −0.02; β = −0.97, 95% CI: −1.83,  −0.08). A negative association was found between LgBDE-28 and birth weight among male infants (β = −253.76, 95% CI: −438.16,  −69.36). PBDE congeners were not associated with head circumference, or gestational age. Our results contribute to growing evidence suggesting that PBDEs have adverse effects on birth outcomes. Highlights: We examined the relations between maternal exposure to PBDEs and birth outcomes. BDE-28, -47, -99, -100, and -153 were detected in serum from 215 pregnant women. There was a negative association between BDE-28, -100 and birth length. BDE-28 showed a negative association with birth weight among male infants. Abstract : Negative associations were found between BDE-28, -100 exposure and birth length as well as between BDE-28 exposure and birth weight in male infants.